Pericarditis and pericardial effusions in the military patient. Issue 3 (6th August 2015) - Cox, Andrew T; Ayalew, Y; White, S; Boos, C J; Haworth, K; Ray, S
Abstract : The pericardium is the thin double-walled sac encapsulating the heart which has a number of important physiological roles including fixing the heart in the mediastinum, protecting it from cross-organ infection (eg, lung) and lubricating cardiac contraction. The pericardium is associated with several disease syndromes that occasionally affect the military population. These include acute and recurrent pericarditis, pericardial effusion and tamponade, which may result from a large number of different aetiological agents. Pericardial diseases have a wide range of clinical manifestations and the diagnosis of pericardial diseases can be a challenge. This article reviews the anatomy and pathophysiology of pericarditis and pericardial effusions before outlining their clinical features, recommended investigations and management options. Particular emphasis is placed on the impact of these diseases for patients in a military occupational environment.